Criminal Liability of Specialist Medical Trainees (PPDS) in Sexual Violence Crimes: Abuse of Power Relations and Judicial Reasoning - Galih Putra Pamungkas; Waluyadi Waluyadi; Gunadi Rasta (PT. Caesarindo Triloka Persada, 2026)
Sexual violence committed by medical professionals within healthcare settings presents a complex legal challenge, blending criminal conduct with the abuse of professional authority and institutional trust. This study analyzes the criminal liability of Specialist Medical Education Program (PPDS) physicians in sexual violence crimes, focusing on the judicial reasoning in Bandung District Court Decision Number 669/Pid.Sus/2025/PN Bdg. Employing a normative juridical method with statutory, conceptual, and case approaches, this research examines the intersection of Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS), Law Number 17 of 2023 concerning Health, and the doctrine of criminal responsibility (geen straf zonder schuld). The findings reveal that the defendant’s dual status as a medical trainee and healthcare provider does not constitute a legal defense or ground for eliminating criminal liability. All statutory elements of sexual violence were fulfilled, accompanied by proven intentionality (dolus), criminal capacity (toerekeningsvatbaarheid), and the absence of exculpatory grounds. Crucially, the court operationalized unequal power relations and the abuse of professional trust as aggravating contextual factors rather than mere background facts. This study concludes that professional medical status entails heightened legal obligations rather than criminal immunity, emphasizing the necessity of integrating criminal prosecution with institutional oversight and victim-centered safeguards in teaching hospitals.